Online problem-based learning and 3D digital books to improve pre-service teachers’ scientific literacy - Sunarti, Titin; Suprapto, Nadi; Prahani, Binar Kurnia; Satriawan, Muhammad; Rizki, Iqbal Ainur (Institute of Advanced Engineering and Science, 2024)
Scientific literacy skill is needed by pre-service physics teachers (PSPTs) since it involves mastering thinking and using scientific thinking in recognizing and addressing social issues. However, low scientific literacy for PSPTs is a problem that needs to be solved, resulting in effectively teaching science to their students. Therefore, to increase the scientific literacy of PSPTs, this study aims to develop an online problem-based learning assisted with digital books with 3D animation (OPBLA3DB). This study employs a quasi-experimental design for educational research with subject 72 PSPTs in one university in Indonesia. The data were collected using written tests, questionnaires, observation sheets, and validity sheets. The findings of this study demonstrate how highly valid and reliable the research tools developed are. The implementation results also show how practical learning is. This teaching model can improve PSPTs’ scientific literacy effectively, along with obtaining positive responses from them. This study implies that the OPBLA3DB model can be widely applied to enhance scientific literacy.